The career costs of children's health shocks - Anne-Lise Breivik; Ana Costa-Ramón (University of Zurich, Department of Economics, 2022)
We provide novel evidence on the impact of a child's health shock on parental labor market outcomes. To identify the causal effect, we leverage long panels of high-quality Finnish and Norwegian administrative data and exploit variation in the timing of the health shock. We do this by comparing parents across families in similar parental and child age cohorts whose children experienced a health shock at different ages. We show that these families have very similar characteristics and were following parallel trends before the event. This allows us to use a simple difference-in-differences model: we construct counterfactuals for treated households with families who experience the same shock a few years later. We find a sharp break in parents' earnings trajectories that becomes visible just after the shock. The negative effect is persistent and stronger for mothers than for fathers. We also document a substantial impact on parents' mental well-being. Our results suggest that the effect on maternal labor earnings results from the combination of the increased time needed to care for the child and the worsening of mothers' mental health.
Keywords: I10; I12; 330; Children; health; mortality; parents; earnings; labor supply; mental health